Delineating the fecal microbiome of healthy domestic short-hair cats in South Korea - Cho, Hyun-Young; Park, Hyung-Joon; Choi, Jin-Sik; Kim, Se-Hoon; Ryu, Min-Ok; Seo, Kyoung-Won (Frontiers in Veterinary Science, 2025)
BackgroundThe gut microbiome is a vital component of an organism’s health, influencing metabolism, immune function, and overall homeostasis. In this study, we aimed to characterize the gut microbiota of healthy domestic short-hair cats in South Korea and evaluate the effects of age, body condition score (BCS), sex, and diet on microbial composition.MethodsFrom August to December 2023, 40 healthy cats aged 1–14 years with a body condition score (BCS) of 5–9 were selected. Cats were excluded if they had taken probiotics or antibiotics, exhibited gastrointestinal symptoms within the last 6 months, or had blood work abnormalities. DNA quantification was performed, and libraries targeting the V3 and V4 regions were prepared according to the Illumina 16S metagenomic sequencing protocol with a read length of 2 × 300 bp. The relative abundance of bacteria at the phylum, genus, and species levels was assessed according to the age, sex, diet, and BCS of the cats, with major bacterial groups selected for chart analysis.ResultsExamination of the fecal samples from 40 healthy cats (aged 0.5–14 years) using 16S rRNA gene sequencing revealed 2,721 bacterial amplicon sequence variants. The predominant phyla were Bacillota, Bacteroidota, and Actinomycetota. Although age did not significantly affect alpha diversity, a trend toward increased diversity was observed in cats aged 7–14 years. Phocaeicola was more abundant in older cats, suggesting a possible association with age-related conditions. Furthermore, Verrucomicrobiota was enriched in cats with a BCS of 8–9, and Ruminococcus torque was positively correlated with higher BCS. Sex-based differences indicated increased levels of Pseudomonadota, Finegoldia magna, and Sutterella massiliensis in neutered males, potentially linked to inflammatory pathways. Dietary analysis revealed an increased abundance of Blautia and Lachnoclostridium following a combination of dry and wet food.ConclusionOur findings provide critical insights into the core microbiota of domestic short-hair cats in South Korea, emphasizing the influence of geographic, physiological, and environmental factors on gut microbial diversity. The results offer a valuable foundation for advancing feline gut health research and enhancing health management strategies for felines, particularly in South Korea.